17. Simultaneous recording of motor related cortical potentials to different basal components of voluntary movements. Issue 12 (December 2016) - Troni, W.; Boretto, F.; Di Sapio, A.; Melillo, F.; Morese, R.; Valentini, M.C.
Abstract : The purpose of the paper was to compare motor related cortical potentials (MRCPs) to basic components of voluntary movements in prolonged recording sessions. EEG activity (27 electrodes placed over the sensorimotor cortex) was recorded in 10 normal volunteers instructed to perform a sequence of 3 simple self-paced movements with the right index finger, separated by an interval of at least 3–4 s: (1) rapid, ballistic-type (Bt-) extension with immediate automated return to resting position; (2) rapid extension (Ex-) to reach and maintain a defined target followed by (3) relaxation (Re-) with passive return to resting position. A prolonged recording session (80 min) provided, for each task, a sequence of 4 MRCPs resulting from the average of 4 successive blocks of 40–80 artefact-free EEG epochs (3 s before and 1 s after onset of individual movements derived from the mechanogram). Recording breaks of about 10–20 s, without interruption of motor task, were interposed at intervals of 3–4 min. Pre- and post-movement components were stable in all MRCPs throughout the recording session. All potentials showed a similar onset and duration of pre-movement components with a similar scalp distribution. Clear-cut differences were observed in the post-movement components probably reflecting different afferent patterns from peripheral effectors.